Menderma Terhadap Sesama sebagai Wujud Menumbuhkan Semangat Kolaborasi Internasional Perguruan Tinggi di Panti Asuhan Walidaina Malaysia: Giving to Others as a Form of Fostering the Spirit of International Collaboration in Higher Education at the Walidaina Orphanage in Malaysia - Hardiyanto, Sigit; Febriyanti, Eka; Zambak, Muhammad Fitra; Saragih, Syaiful Amri; Siregar, Muhammad Said; Hadipramana, Josef; Nasution, Muhammad Irfan; Mohamad, Hafizal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Universities have a social responsibility to contribute to the progress of society, not only at the local or national level but also at the global level. This form of collaboration is carried out with partners such as overseas orphanages which can overcome obstacles and problems in realizing the synergy of the three dharmas of higher education by providing clean and healthy living behavior programs through personal hygiene health education activities in the orphanage environment to increase knowledge among children in the orphanage. The activity method focuses on interaction by providing counseling to increase knowledge about the importance of clean and healthy living behavior (PHBS) as an effort to strengthen a clean culture that prioritizes health. The service to the international community carried out collaboratively between the Muhammadiyah University of North Sumatra and the Universiti Sains Islam Malaysia went smoothly and provided positive feedback and results to the children in the orphanage, including cognitive abilities as the main capital to improve the experience and quality of health education for children in the orphanage.